Going Forward : The Evolution of Quebec's English-Speaking Community - Jedwab, Jack (Canada. Office of the Comissioner of Official Languages, 2004)
This report characterizes, in the most detailed presentation to date, the Quebec Anglophone population and its evolution over time. It speaks to the community’s residential patterns, mobility, diversity and institutional characteristics. Employing a rich body of demographic, statistical and attitudinal data from census and other sources, it provides a portrait of the Anglophone population at the turn of the new century that aids a wider understanding of the community. The study also focusses on how Quebec’s English speakers perceive their current priorities and vision of the future.
Keywords: Official Language Minority Community (OLMC)

Vers l'avant : L'évolution de la communauté d'expression anglaise du Québec - Jedwab, Jack (Canada. Office of the Comissioner of Official Languages, 2004)
Le présent rapport se veut la description la plus détaillée et actualisée des caractéristiques de la population anglophone du Québec, notamment en ce qui concerne ses modèles résidentiels, sa mobilité, sa diversité et ses institutions. Fondé sur un vaste ensemble de données démographiques, statistiques et attitudinales tirées du recensement et d’autres sources, il brosse un tableau complet de la population anglophone au tournant du nouveau siècle et vise à mieux faire comprendre cette communauté. Le rapport s’attache aussi à la perception qu’ont les anglophones de leurs priorités actuelles et à leur vison de l’avenir.
Keywords: Official Language Minority Community (OLMC)